Displacement of the proximal tendon of the long digital extensor muscle - de Rooster, H.; Risselada, M.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
A case of bilateral displacement of the proximal tendon of the long digital extensor (LDE) muscle has been described in a 5-year-old Siberian Husky. During surgery, a prosthetic roof was created over the extensor sulcus of the proximal tibia on both legs simultaneously.
Keywords: Long digital extensor; tendon; displacement; stifle; dog